Comparative evaluation of treatment methods of neoadjuvant intra-arterial chemotherapy and chemoembolization by drug-saturated embospheres in II–IVa stages cervical cancer - Sh. G. Parsyan; A. S. Lisyanskaya; M. A. Kukanov; O. A. Smirnova; M. S. Shushaniya; G. M. Manikhas (Опухоли женской репродуктивной системы)
Objective: comparative evaluation of treatment methods for neoadjuvant intra-arterial chemotherapy and chemoembolization by drug-saturated microspheres followed by surgical treatment in II–IVa stages cervical cancer.Materials and methods. This study presents the results of complex treatment in 209 patients (average age – 40.57 ± 8 years) with II– IVa stages cervical cancer and 384 endovascular interventions as the first stage of complex treatment in the period from 2010 to 2016. The scheme neoadjuvant intra-arterial chemotherapy was carboplatin (AUC6 intra-arterial) + irinotecan (200 mg/m2 intravenously on day 1) every 21 days. Radical surgical treatment was performed basically after 2 cycles of chemotherapy. Patients who did not respond sufficiently to neoadjuvant intra-arterial chemotherapy underwent a radical course of chemoradiation therapy according to the standard scheme.Results. The overall response to neoadjuvant intra-arterial chemotherapy was 84.8 % and 79 % of patients in groups of chemoinfusion and trans-arterial chemoembolization, respectively (p >0.05). Operability was higher in group of chemoinfusion (69 % versus 46.4 %) (p <0.01), and fewer patients with metastases to regional lymph nodes were revealed in this group (30.2 % versus 42 %), p <0.05. Overall and survival rate is statistically significantly better in group of chemoinfusion – 63.9 % and 61 % versus 43 % and 42 %, respectively, p <0.05. At the same time, statistically significant differences between the groups were revealed only at stages III–IVа cervical cancer. Radically operated patients, as expected, had a better prognosis (p <0.001). The age of patients, tumor differentiation and therapeutic pathomorphosis did not affect the prognosis of life.Conclusions. Neoadjuvant intra-arterial chemoinfusion and chemoembolization using irinotecan + carboplatin scheme are relatively safe treatment methods with acceptable toxicity and have a high cytotoxic effect. Patients in chemoinfusion group have a better prognosis compared with patients in chemoembolization group. Selective chemoembolization with subsequent surgical treatment or radiation therapy may be the treatment of choice for stage II cervical cancer complicated by bleeding.